2016
DOI: 10.1371/journal.pone.0158269
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Di-Leucine Motif at the N-Terminus of Human Organic Solute Transporter Beta Is Essential for Protein Association and Membrane Localization

Abstract: The heteromeric membrane protein Organic Solute Transporter alpha/beta is the major bile acid efflux transporter in the intestine. Physical association of its alpha and beta subunits is essential for their polarized basolateral membrane localization and function in the transport of bile acids and other organic solutes. We identified a highly conserved acidic dileucine motif (-EL20L21EE) at the extracellular amino-tail of organic solute transporter beta from multiple species. To characterize the role of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…4a). Among them, the dileucine motif is of high interest because its importance in targeting transmembrane proteins to the endosome/lysosome system and TGN [3338]. Although several di-leucine motifs are present in PRV pUL56, our data showed that none had the ability to target pUL56 to the TGN.…”
Section: Discussionmentioning
confidence: 72%
“…4a). Among them, the dileucine motif is of high interest because its importance in targeting transmembrane proteins to the endosome/lysosome system and TGN [3338]. Although several di-leucine motifs are present in PRV pUL56, our data showed that none had the ability to target pUL56 to the TGN.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the dileucine determinant at the C terminus of the luteinizing hormone b subunit prevents its increased trafficking and exocytosis (48). In contrast, the substitution of a dileucine motif impairs the membrane localization of the Organic Soluble Transporter (44). Our study now introduces CaM into this debate because Kv1.3, KCNE4, and CaM are in a tight relationship.…”
mentioning
confidence: 78%
“…We identified a tetraleucine motif within the C-terminal domain of KCNE4 that mediates the association with Kv1.3. Interestingly, dileucine motifs promote endocytosis, protein-protein interactions, and basolateral trafficking (43)(44)(45)(46). Altering the KCNE4 tetraleucine motif, as well as the suppression of the ERRM, improved the peptide targeting to the plasma membrane.…”
mentioning
confidence: 99%
“…Two other studies reported a modest one-to-fivefold increase in OST␣ mRNA in extrahepatic cholestasis and PBC (7,51). The constant OST␣ mRNA, but increased OST␣ protein, can be explained by the fact that OST␣ protein is unstable without OST␤ protein (14,40,60). In liver tissue from NASH patients and patients with PBC, OST␤ mRNA and protein are remarkably induced, which enables OST␣-OST␤ complex formation.…”
Section: G604mentioning
confidence: 96%